2021
DOI: 10.1088/1742-6596/1900/1/012006
|View full text |Cite
|
Sign up to set email alerts
|

Estimating The Efficiency Of Phagocytic Neutrophil Cells And Studying Its Risk Factors Among Diabetic Foot Ulcers

Abstract: There are several factors that affect the efficiency of phagocytic activity in diabetic patients. In this study, a significant difference of phagocytosis efficiency showed in diabetic patients and controls (non-diabetic). The means of phagocytic activity were 43.05%, 52.70% and 71.35% for diabetic foot ulcer, diabetes mellitus patients and controls respectively. Age groups, mean blood glucose levels and controlling fasting blood glucose were significant factors effects on phagocytic activity (P-value = 0.022, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In our study, no metastatic infection with the source of PLA was found in patients with hypervirulent K. pneumoniae- related pyogenic liver abscess, whereas this phenomenon has been reported in previous studies ( Fung et al., 2002 ; Tan et al., 2004 ; Sun et al., 2021 ). Diabetes is a known predisposing factor for impaired neutrophil chemotaxis and phagocytosis ( Baras and Bin-Hameed, 2021 ). Patients with metastatic infections are usually diabetic, but some of them with metastatic infections by hvKp strains are healthy and have no history of diabetes, so another important factor may be involved in this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, no metastatic infection with the source of PLA was found in patients with hypervirulent K. pneumoniae- related pyogenic liver abscess, whereas this phenomenon has been reported in previous studies ( Fung et al., 2002 ; Tan et al., 2004 ; Sun et al., 2021 ). Diabetes is a known predisposing factor for impaired neutrophil chemotaxis and phagocytosis ( Baras and Bin-Hameed, 2021 ). Patients with metastatic infections are usually diabetic, but some of them with metastatic infections by hvKp strains are healthy and have no history of diabetes, so another important factor may be involved in this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed analyses of ulcer characteristics, such as stages and phagocytic movement efficiency, are contributing to the field. Researchers also explore innovative treatments, including hyperbaric oxygen therapy and placental-derived products, to address challenges like polymicrobial infections [4].…”
Section: Analog To Digital Converters and The Clinicalmentioning
confidence: 99%